Prognostic impact of tumor-infiltrating lymphocytes in non-small cell lung carcinomas. (February 2022) - Mlika, Mona; Saidi, Ayoub; Mejri, Nesrine; Abdennadher, Mehdi; Haddouchi, Chokri; Labidi, Soumeya; Khiari, Hyem; Boussen, Hamouda; Hsairi, Mohamed; Mezni, Faouzi
Introduction: Tumor-infiltrating lymphocytes represent a pivotal component of the host anti-tumor response. Thus, they considerably influence the evolution of cancers including non-small cell lung carcinomas. Even if, this important role is consensual, many discordant results are published in the literature about the prognostic role of the different populations of tumor-infiltrating lymphocytes. The aim of our work was to evaluate the prognostic impact of CD8+, CD4+, and forkhead box protein P3+ lymphocytes in the tumor microenvironment of non-small cell lung carcinomas. Methods: We conducted a retrospective descriptive study, which included non-small cell lung carcinomas diagnosed in the department of pathology and followed in the medical oncology department of the same hospital between 2011 and 2015. Tumor-infiltrating lymphocytes were analyzed by the immunohistochemical method for forkhead box protein P3, CD4, and CD8. Intratumoral and stromal-labeled lymphocytes were quantified by manual counting at high magnification (×400). Forkhead box protein P3+/CD8+, forkhead box protein P3+/CD4+, and CD8+/CD4+ ratios were subsequently calculated. The prognostic value of tumor-infiltrating lymphocytes was assessed in respect of overall survival, recurrence-free survival, and relapse-free survival. Results: Thirty-nine patients were included. The mean age of patients was 59.6 years. A complete surgical resection ( p = 0.009), and a CD8/CD4 ratio ( p = 0.008) were prognostic factors for overall survival. Complete surgical resection ( p = 0.003), the forkhead box protein P3/CD8 ( p = 0.005), and forkhead box protein P3/CD4 ( p = 0.037) ratios were prognostic factors for recurrence-free survival. The CD8+ tumor-infiltrating lymphocytes rate ( p = 0.037) was a prognostic factor for relapse-free survival with a threshold of 67.8/high power field. Microscopic subtype ( p = 0.037) was a prognostic factor for relapse-free survival when only adenocarcinoma and squamous cell carcinoma were considered. In multivariate analysis, age ( p = 0.004) and a CD8/CD4 ratio ( p = 0.016) were independent predictors of overall survival. Conclusion: Despite the limitations of our study, our results confirm the prognostic value of tumor-infiltrating lymphocytes in non-small cell lung carcinomas and the importance of the combined quantification of their different subpopulations.